1997
DOI: 10.1111/j.1532-950x.1997.tb00517.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Wound Lavage Solutions on Canine Fibroblasts: An In Vitro Study

Abstract: Further clinical investigation is indicated to establish whether Ringer's lactate is the wound lavage solution of choice compared with normal saline. Sterile tap water may cause considerable fibroblast injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 11 publications
(3 reference statements)
1
10
0
2
Order By: Relevance
“…Physiological saline showed better wound healing effect than non-physiological tap water and an antiseptic in this study as is shown in table two. This corroborates the work of Buffa et al (1997) who showed that canine fibroblast had more damage with tap water than with normal saline. Other workers have documented this effect of normal saline on healing wounds but the mechanism of this effect is presently not known (Jacobson and Lineaweaver et al, 1985).…”
Section: Discussionsupporting
confidence: 91%
“…Physiological saline showed better wound healing effect than non-physiological tap water and an antiseptic in this study as is shown in table two. This corroborates the work of Buffa et al (1997) who showed that canine fibroblast had more damage with tap water than with normal saline. Other workers have documented this effect of normal saline on healing wounds but the mechanism of this effect is presently not known (Jacobson and Lineaweaver et al, 1985).…”
Section: Discussionsupporting
confidence: 91%
“…There appears to be growing evidence to suggest that a completely sterile wound is at a disadvantage (Inflammation and Wound Healing, 2004), supporting the concept that physical removal to a level below the threshold for infection (around 10 5 bacteria per cm 2 depending upon virulence) is our goal. Removal of excessive bacterial burden rather than complete annihilation using a toxic solution would appear to be the preferential approach (Buffa et al, 1997).…”
Section: Back To the Dark Ages: Cleansing Wounds From The Sensible Tomentioning
confidence: 99%
“…Lavage [11][12][13] Die Wundspülung ist ein wichtiger Aspekt der Wundbehandlung. Sie hilft, die bakterielle Kontamination zu verringern und entfernt Fremdkörper sowie anderes loses Material aus der Wunde.…”
Section: Offenes Wundmanagementunclassified
“…Die Spülung sollte mit körperwarmer Ringer-Lösung oder Polyhexaniden (Prontovet ® ) durchgeführt werden. Eine In-vivo-Studie konnte zeigen, dass Leitungswasser und sterile Kochsalzlösung zytotoxisch für Fibroblasten sind [11]. Antiseptika sollten vermieden werden, da sie ebenfalls zytotoxisch für das Wundbett sind und den Heilungsprozess behindern [12].…”
Section: Offenes Wundmanagementunclassified